Le rôle des milieux de presse dans la fondation de l’Etat belge et la création d’une « opinion publique » nationale (1830-1860) - Pierre Van den Dungen (Amnis)
From the 1820s on, French-speaking men of letters were writing opposition press in the kingdom of the Netherlands of William of Orange. These opinion-piece writers established themselves as ‘patriots’ and Belgians fighting against the Dutch government press and its wage-earning publicists publicists. Major actors in the Belgian Revolution of 1830, they rose to hold important office in the new State. They immediately enshrined freedom of the press into the Constitution. They wished this freedom to be (almost) absolute whilst their individual professional lives provided a demanding definition of the ‘métier’ of journalist. To their minds, freedom of speech was above all a duty of the press. It was a matter of using the newspapers to form public opinion, as widely as possible, in favour of political liberalism. Despite various attempts by the new rulers – including one to create an unofficial daily – on the contrary, freedom of the press revealed (and encouraged) plurality of opinions amongst the circles espousing these new ideas. From this point on, we witness a ‘quarrel of the patriots’ in many publications. However, pressure by leaders of the great nations –headed by France – constituted a much more serious threat. They did not look kindly upon the existence of a minor country whose press was free … to criticise them. Under Napoléon III, the will of the French authorities to put a stop to what they qualified as licence was such that Belgian national integrity was momentarily in peril. In this instance, the attitude of the Belgians would once again testify to the existence of an organic link between the freedom of the press and national sentiment.